Macroprolactinemia in Patients with Prolactinomas: Prevalence and Clinical Significance - Elenkova, А.; Genov, N.; Abadzhieva, Z.; Kirilov, G.; Vasilev, V.; Kalinov, K.; Zacharieva, S. (Experimental and Clinical Endocrinology & Diabetes, 2013)
Data on the prevalence of macroprolactinemia in patients with prolactinomas is quite limited as the presence of high-molecular prolactin forms is suspected mainly in subjects with mild hyperprolactinemia and negative pituitary imaging.The main objective of this observational case-control study was to assess the prevalence and clinical significance of macroprolactinemia among patients with prolactinomas.The study population consisted of 239 subjects: 131 prolactinoma patients and 108 sex-, age- and ethnicity– matched healthy controls. Macroprolactinemia was defined by a PRL recovery after PEG precipitation of<40%.The prevalence of macroprolactinemia among newly diagnosed prolactinoma patients did not differ statistically from the prevalence in the control group (3.5 vs. 3.7%; p=1.000) but was lower although non-significantly than the subgroup of patients treated with dopamine agonists (DA) (3.5 vs.10.8%; p=0.072). Significant association between disruptions of ovarian function and serum levels of the monomeric as well as high-molecular prolactin isoform was found.In few cases, the presence of typical hyperprolactinemia-related clinical symptoms and their disappearance after treatment with DA suggests biological activity of macroprolactin comparable with that of monomeric prolactin isoform. Decrease of macroprolactin levels after DA treatment could suggest tumoral origin of the high-molecular isoform in these rare cases. Although macroprolactinemia is considered a benign condition, pituitary imaging, DA treatment, and prolonged follow-up may be necessary in certain cases. An individualized approach to the management of patients with macroprolactinemia should be applied.
Keywords: macroprolactinemia; PEG-precipitation test; prolactinoma